A study on the status of the technological level of the Philippine garment manufacturing industry as perceived by the UP BSCT graduates - Gasapos, Marishiel F.
BS Clothing Technology is UP's response to the needs and demands of the garment industry which provides clothing, one of man's basic needs. This study aims to determine the perceptions of the BSCT graduates on the technological level of the Philippine garment manufacturing industry. This will also serve as feedback regarding the necessity of education and discover hoe the BSCT program helped them in coping with these innovations. A descriptive study was conducted by using a survey. A questionnaire was answered by 20 BSCT graduates who are active in the industry. This researcher made tool will determine their perceptions about the technologies present in the industry and how the BSCT program prepared them. Majority of their answers showed that the garment industry is not yet fully developed in terms of technology. According to 14 respondents, government is not supportive. Meanwhile, 12 out of 20 of the respondents find these new innovations as too expensive for the Philippine market although many pointed out that it will be cost efficient in the long run. Continuous education of people in the industry specially in the production aspect were most of the innovations are geared towards are highly advised to further upgrade its present condition. Majority of the respondents, 90% agreed that BSCT gave them a well rounded education in the field of garments and textiles, from general to specific. Improvement in the curriculum in terms of providing a more updated course outline and more exposure in the innovations present in the industry specially the Computer -aided manufacturing (CAM) system will be beneficial to future students.